2020
DOI: 10.1039/d0sc02060e
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Aβ40 and Aβ42 in amyloid plaques with a small molecule fluorescence probe

Abstract: A small molecule fluorescence probe ICTAD-1 was rationally designed for differentiating Aβ40 and Aβ42 in solutions and in Aβ plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…As shown in Figure 3 B, the fluorescence intensity of probe 2 could linearly correlate with Aβ monomers, oligomers and aggregates at a concentration range of 100 nM-6.4 μM, 50 nM-3.2 μM and 100 nM-10 μM, respectively. The LOD (3σ/k) was then calculated to be ~14.1, ~12.8 and ~12.9 nM for the monomers, oligomers and aggregates, respectively, which were comparable to that of other previously reported fluorescent probes for Aβ aggregates 28 , 49 - 53 . Third, the examination of the selectivity toward the Aβ proteins over other representative endogenous species, including L -Cysteine, glutathione, vitamin C, Cytochrome C, BSA, AChE, BuChE, Amylin, hMAO-A, β-Galactosidase, and reactive oxygen species (hydroxyl radical, singlet oxygen, superoxide radical, and H 2 O 2 ) showed that strong fluorescence could be observed only in the presence of Aβ monomers, oligomers or aggregates; negligible fluorescence appeared toward other examined species, especially Amylin or BSA, which were found to be notorious species potentially competing with the Aβ species in the brain (Figure 3 C).…”
Section: Resultssupporting
confidence: 80%
“…As shown in Figure 3 B, the fluorescence intensity of probe 2 could linearly correlate with Aβ monomers, oligomers and aggregates at a concentration range of 100 nM-6.4 μM, 50 nM-3.2 μM and 100 nM-10 μM, respectively. The LOD (3σ/k) was then calculated to be ~14.1, ~12.8 and ~12.9 nM for the monomers, oligomers and aggregates, respectively, which were comparable to that of other previously reported fluorescent probes for Aβ aggregates 28 , 49 - 53 . Third, the examination of the selectivity toward the Aβ proteins over other representative endogenous species, including L -Cysteine, glutathione, vitamin C, Cytochrome C, BSA, AChE, BuChE, Amylin, hMAO-A, β-Galactosidase, and reactive oxygen species (hydroxyl radical, singlet oxygen, superoxide radical, and H 2 O 2 ) showed that strong fluorescence could be observed only in the presence of Aβ monomers, oligomers or aggregates; negligible fluorescence appeared toward other examined species, especially Amylin or BSA, which were found to be notorious species potentially competing with the Aβ species in the brain (Figure 3 C).…”
Section: Resultssupporting
confidence: 80%
“…More specifically, they can form hydrogen bonds and salt bridges with the amino acids Asp1 and Ala42. Their binding motif is similar to that of the fluorescent probe reported by the Ran group, which can differentiate Aβ42 fibrils and Aβ40 fibrils by targeting the extra two amino acids at the C terminal of the Aβ42 fibrils, suggesting that ZY-17-DT and ZY-17-OMe might also have a different binding affinity towards Aβ42 vs. Aβ40 fibrils 42.…”
supporting
confidence: 71%
“…[ 175 ] Development of novel A β plaque‐targeting fluorescent imaging agents has become a hot topic. [ 176,177 ] Marzano et al investigated an acrylonitrile derivative 118 (Figure 20) for aggregation‐induced emission properties as a fluorescent imaging agent to detect amyloid fibrils. It was reported that this compound stained oligomeric and pre‐fibrillar species of amyloidogenic α ‐synuclein with higher affinity compared to thioflavin‐T.…”
Section: Biological Activities Of Acrylonitrilesmentioning
confidence: 99%